Influence of Temperature and Pressure on the Lattice Constant of SrTiO3 Perovskite by the Statistical Moment Method with Improved Interatomic Potential - Phuong, Cao Huy; Hung, Vu Van (VNU Journal of Science: Mathematics - Physics, 2022)
Temperature and pressure dependence of lattice constants of a cubic Strontium Titanate (SrTiO 3 ) has been investigated using the statistical moment method. The lattice constants at various temperatures is derived in closed analytic form by including the anharmonic effects of the lattice vibrations explicitly. The potential with the partial charge model and Morse function is used. The numerical lattice constants at high temperatures by the statistical moment method are in good and reasonable agreement with the other theories and the experimental data. Variations of the lattice parameter of SrTiO 3 with the temperature are obtained at 1 atm, 8.2 GPa, and 15.2 GPa.  Increasing of the lattice constants with increasing temperature is due to enhancing atomic anharmonic fluctuations in SrTiO 3 lattice crystal at higher temperature. A decrease of the lattice constants with increasing pressure can be demonstrated by the reduction of atomic vibrations in SrTiO 3 crystal lattice at higher pressures.